Psychological Distress and Subsequent Cardiovascular Events in Individuals With Coronary Artery Disease. Issue 9 (7th May 2019) - Pimple, Pratik; Lima, Bruno B.; Hammadah, Muhammad; Wilmot, Kobina; Ramadan, Ronnie; Levantsevych, Oleksiy; Sullivan, Samaah; Kim, Jeong Hwan; Kaseer, Belal; Shah, Amit J.; Ward, Laura; Raggi, Paolo; et al.
Abstract : Background: Higher symptom levels of a variety of measures of emotional distress have been associated with cardiovascular disease (CVD), especially among women. Here, our goal was to investigate the association between a composite measure of psychological distress and incident cardiovascular events. Methods and Results: In a prospective cohort study, we assessed 662 individuals (28% women; 30% blacks) with stable coronary artery disease. We used a composite score of psychological distress derived through summation of Z‐transformed psychological distress symptom scales (depression, posttraumatic stress, anxiety, anger, hostility, and perceived stress) as a predictor of an adjudicated composite end point of adverse events (cardiovascular death, myocardial infarction, stroke, heart failure, or unstable angina). During a mean follow‐up of 2.8 years, 120 (18%) subjects developed CVD events. In the overall population, there was no association between the psychological distress measure and CVD events, but there was a sex‐based interaction ( P =0.004). In women, higher psychological distress was associated with a higher incidence of CVD events; each SD increase in the composite score of psychological distress was associated with 1.44 times adjusted hazard of CVD events (95% CI, 1.09–1.92). No such association was found in men. Conclusions: Among patients with coronary artery disease, higher psychological distress is associated with future cardiovascular events in women only.